Religion around Shakespeare - Kaufman, Peter Iver (University Park, Pennsylvania : The Pennsylvania State University Press, 2013)
"Examines the historic and religious context surrounding the work of William Shakespeare"--Provided by publisher.
Religion around -- Around shakespeare -- Interlude -- Religious authority -- Religious personality -- Religious community.
Includes bibliographical references (pages 223-245) and index.
Description based on print version record.
Keywords: Shakespeare, William, -- 1564-1616 -- Religion; England -- Church history -- 16th century; England -- Church history -- 17th century; Christianity and literature -- England -- History -- 16th century; Christianity and literature -- England -- History -- 17th century; Religion in literature; DRAMA / English, Irish, Scottish, Welsh; Electronic books